Atomistic simulations of 40Ar diffusion in muscovite. (15th August 2022) - Nteme, Jehiel; Scaillet, Stéphane; Brault, Pascal; Tassan-Got, Laurent
Abstract: Muscovite ranks among the most commonly dated minerals in 40 Ar/ 39 Ar geochronology. Yet, its use in thermochronological reconstructions is hampered by the lack of reliable data on its 40 Ar diffusional behavior. In this contribution, we investigate 40 Ar lattice diffusion in muscovite at the atomic scale using Molecular Dynamics (MD) simulations combined with Nudged Elastic Band (NEB) and Transition State Theory (TST). Classical MD simulations of 40 Ar recoil dynamics in 2 M 1 muscovite reveal that 40 Ar initially resides predominantly in the interlayer region, close to its production site. Systematic computations of migration barriers coupling NEB with TST identify the divacancy mechanism as the more energetically favorable pathway for 40 Ar diffusion in the interlayer region, with characteristic activation energy E = 66 kcal.mol −1 and frequency factor D 0 = 6 × 10 - 4 cm 2 .s −1 . For typical cooling rates between 1–100 ° C.Ma −1 and grain size varying from 0.1 and 1 mm, these parameters predict closure temperatures significantly higher ( ∼ 200 ° C) than currently accepted maximum estimates ( ∼ 500 ° C). Consistent with long-standing empirical evidence, our theoretical results downplay the role of purely thermally activated diffusion in promoting efficient 40 Ar transport in ideal (stoichiometrically stable and undefective) muscovite. Along with experimental and field-based evidence, they call for more complex physics to explain the 40 Ar retention properties of natural muscovite, most notably by considering crystal-chemical disequilibrium interactions and the reactivity of the interlayer with the external medium.